Exploring robustness of hybrid membranes under high hydrostatic pressure and temperature - Tamby, Anandi; Sahonero-Canavesi, Diana X.; Villanueva, Laura (Frontiers in Microbiology, 2024)
Bacterial membranes are typically composed of ester-bonded fatty acid (FA), while archaeal membranes consist of ether-bonded isoprenoids, differentiation referred to as the ‘lipid divide’. Some exceptions to this rule are bacteria harboring ether-bonded membrane lipids. Previous research engineered the bacterium Escherichia coli to synthesize archaeal isoprenoid-based ether-bonded lipids together with the bacterial FA ester-linked lipids, showing that heterochiral membranes are stable and more robust to temperature, cold shock, and solvents. However, the impact of ether-bonded lipids, either bacterial or archaeal, on membrane robustness, remains unclear. Here, we investigated the robustness, as survival after shock, of E. coli synthesizing either archaeal or bacterial ether-bonded membrane lipids, under high temperature and/or high hydrostatic pressure (HHP). Our findings reveal E. coli with bacterial ether-bonded lipids is more robust under HHP and high temperature. On the contrary, the presence of archaeal ether-bonded membrane lipids in E. coli does not affect the robustness under HHP nor high temperature under the tested conditions. We observed morphological changes induced by the shock treatments including reduced length under high temperature or HHP, and the presence of elongated cells after a shock of HHP and high temperature combined, suggesting the combined treatments impaired cell division. Our results contribute to a deeper understanding of membrane adaptation to extreme environmental conditions and highlight the significance of HHP as a key parameter to investigate the differentiation of membranes during the lipid divide.